Effectiveness of CBLS to improve PHP programming for beginners in higher learning institutions - Abdullahi, Mohamud Sheikh Ibrahim (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Cloud Based Learning Systems (CBLS) refers to the systems that provide electronic or online contents to enable the learning process by offering tools and functionalities on the platform available in Cloud. All the contents and functionalities of the system are available as services that can be accessed anywhere through internet. The systematic literature review (SLR) conducted in this study discovered that there is a lack of empirical studies in terms of understanding CBLS's effectiveness particularly for learning programming. Therefore, this research seeks to examine the effectiveness of CBLS systems in PHP programming skills among higher education students by measuring students' performance in solving programming problems. In this study, three single-subject experiments were conducted using 40 undergraduate students in Web Programming course. The experiments compared the time students spent to solve programming tasks by using traditional learning method and CBLS. A survey to measure students' self-efficacy was administered before and after the experiments. The findings of this study showed that there is a statistically significant difference in learning PHP programming using CBLS when compared with traditional method. Our experiment results showed that students solve programming problems in less time when using CBLS. The study also found out that CBLS is effective for improving students' self-efficacy.